Alienation in the Implementation of Public Services Mall Policy (MPP) in Banyumas Regency - Ranjani Ranjani Ranjani; Ratminto Ratminto Ratminto; Alizar Isna Isna (Sekolah Tinggi Ilmu Administrasi Lembaga Administrasi Negara, 2023)
Policy alienation was developed to better understand the experience of frontline public professionals with new policies. The study of policy alienation examines the problems that arise from the implementation of certain policies. The implementation of the Public Service Mall policy is intended to unite services from the central government, local government and private sector in one place. This research focuses on alienation in policy implementation, especially on the implementation of the Public Service Mall (MPP) policy in the Banyumas Regency. The research method used in this study is qualitative. The data analysis method used is an interactive analysis model. The results of the study indicate that policy alienation in the implementation of the Public Service Mall policy in Banyumas Regency does not occur spontaneously, but because of the emergence of various reactions and events on the implementation of the Public Service Mall policy in Banyumas Regency through various actions, such as refusal to integrate licensing and non-licensing services from several agencies. Then, another reason is the limited authority possessed by public employees in MPP. Another factor behind the occurrence of policy alienation in the implementation of the Banyumas Regency Public Service Mall is the limited budget and human resources.